The Role of Film Sensor Institutions on Film Show to Foreign Film Platform - Raissa, Amanda; Sukendar, AstriaYuliSatyarini; Michael, Tomy (International Journal of Psychosocial Rehabilitation, 2020)
In this day and age access to everything related to technology can be accessed quickly and easily by the people or community. The technology presented in this case, one no longer needs to be difficult or spend time to go to malls and shopping centers to watch films that are still freshly screened in theaters, this is because in times of sophistication, a lot of movie platforms that provide various kinds of films that can be watched freely but still paid and also legal, with the freedom of someone to access film shows and reality shows, in this case problems arise in terms of film censorship and also other shows provided by the foreign film platform. Therefore, in this article the author will examine the process of censoring impressions from foreign film streaming platforms in Indonesia.The method of approach used in this article is normative empiricism in which the writer will mix and match the realities that occur in the community with the applicable laws and regulations. The results of this study are that Indonesia has the right to censor every film showing in its country in accordance with Law Number 33 of 2009 concerning Film.